(untitled) (Indian Journal of Animal Production and Management, 2017)
Traditional bio-gas digesters like floating drum and fixed dome were compared with two new digester designs, horizontal and vertical flow type, for their efficiency in bio-gas production using cattle dung as substrate. The result obtained showed that; the horizontal flow type digester had maximum bio-gas production efficiency in comparison to all other digesters. The bio-gas production in horizontal flow type digester was significantly (p< 0.001) higher than vertical flow type and old models like floating drum and fixed dome type digesters.